Role of hematological parameters in the early diagnosis of neonatal sepsis - Niyati Shah; Hardik Gandhi; Ravikumar Mansuriya; Alpesh Maru; Gunvanti Rathod; Pragnesh Parmar (Wolters Kluwer Medknow Publications, 2024)
The major cause of neonatal mortality and morbidity is bacterial sepsis. Blood culture is the most reliable method in neonatal sepsis. This study was conducted to study the usefulness of hematological parameters in the early diagnosis of neonatal sepsis and to assess the most sensitive and specific variables in diagnosing neonatal sepsis. This prospective study was conducted in a tertiary care hospital from January 2017 to January 2018. Peripheral blood smears were prepared from patients with clinical suspicion of sepsis or predisposing perinatal factors for sepsis and stained with Field's stain and examined. The hematological findings were analyzed according to the hematologic scoring system of Rodwell. It was found that immature PMN count, I:M ratio, and I:T ratio had the highest sensitivity (92.06%, 87.30%, and 74.60%, respectively) while I:M ratio, I:T ratio, and degenerative changes in PMN had the highest specificity (97.50%, 96.50%, and 94.0%, respectively) in the prediction of sepsis.